3tayer - Fraihat, Bara'a (My University, 2018)
Deals Store an online store, web based application, which allows customers order product online , also they can find a product of interest by searching for the name of product , it's price or it's category . On hand the trader can offer his products in the store , then after offer the product he can modify the offer or delete it and on the other hand the trader can buy products from another trader. In the system there is the administrator who can manage the whole website (he has all privileges) this administrator is the owner of the company .
Keywords: 3tayer,markiting online,online